Perception index of environmental education in fundamental education schools in a city on the Brazil / Bolivia frontier - Paraguassú-Chaves, Carlos Alberto; Cavalcante, Fábio Robson Casara; Trindade, Carla Dolezel; Filho, Simão Aznar; Cavalcante, Ana Maria Morais da Fonsêca; Góes, Sílvia Bezerra de; Costa, Vitor Akira Uesugui; Almeida, Fabrício Moraes de; Dantas, Lenita Rodrigues Moreira (International Journal for Innovation Education and Research, 2021)
Objective: to analyze the Environmental Education Perception Index in the light of national curricular parameters (PCN’s) within the scope of elementary education in state schools in the city of Guajará-Mirim, Rondônia, on the Brazil / Bolivia border. Method: for this study, factor analysis was used as a mechanism for building performance indices for each parameter studied. The Statistical Package for the Social Sciences - SPSS [30] tool was used to determine the proposed indexes that followed the scale advocated by Hair et al [21]. Results: the results presented by the teachers of the 4 schools correspond to the perception index considered “good” with an average index of 0.699. The average perception index of school technicians and managers was 0.591, considered a “regular” index. The students had an average performance of 0.537, considered a “regular” performance index. The general IPEA among all schools surveyed was considered “regular” with a performance index of 0.597. Conclusion: the fact that Guajará-Mirim has 92% of its territory occupied by Conservation Units and Indigenous Lands and a strong environmental policy does not correspond to the level of abstraction applied by formal Environmental Education. Environmental Education given in Guajará-Mirim elementary schools imposes considerable risks on the environmental conscience of future generations, as it presents certain deficiencies in fulfilling its institutional role as a social transformer, configuring itself as a limiter of sustainable development and awareness environmental.